2016
DOI: 10.1039/c5ra20718e
|View full text |Cite
|
Sign up to set email alerts
|

Copper NPs supported on hematite as magnetically recoverable nanocatalysts for a one-pot synthesis of aminoindolizines and pyrrolo[1,2-a]quinolines

Abstract: Copper mixed oxide NPs supported on a hematite surface were achieved using a facile hydrothermal method in a single step. The catalytic potential of the Cu@Fe2O3 NPs was explored for the synthesis of aminoindolizines and pyrrolo[1,2-a]quinolines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…In 2016, for the first time, Rawat et al. reported the formation of the CuO/Cu 2 O mixed oxides supported on hematite (Cu@Fe 2 O 3 ) through hydrothermal method in a single step . Then, the Cu@Fe 2 O 3 MNPs were used to catalyze A 3 coupling reactions of aldehydes, alkynes and amines in glycerin at 110 °C (Scheme ).…”
Section: The Various Catalytic Systems For A3 Coupling Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, for the first time, Rawat et al. reported the formation of the CuO/Cu 2 O mixed oxides supported on hematite (Cu@Fe 2 O 3 ) through hydrothermal method in a single step . Then, the Cu@Fe 2 O 3 MNPs were used to catalyze A 3 coupling reactions of aldehydes, alkynes and amines in glycerin at 110 °C (Scheme ).…”
Section: The Various Catalytic Systems For A3 Coupling Reactionsmentioning
confidence: 99%
“…It is important to stress that despite huge advancements of the reported works in the literature, another important challenges in the A 3 coupling reactions is nature of solvent and kind of the catalyst. A number of nanocatalysts, including copper, silver, gold, nickel, magnetic nanocatalysts and Co 3 O 4 , ZnS and nanopowder zinc titanate were successfully applied for A 3 coupling reactions with yields ranging from good to excellent in appropriate times in organic solvents or aqueous medium . The authors ascribed high catalytic activity of nanocatalysts to the particles size.…”
Section: Outlook and Conclusionmentioning
confidence: 99%
“…In continuation of our work to develop alternative catalytic approaches, we report herein a simple, eco‐friendly, cost effective and time efficient synthesis of 2‐alkenylated 1,3‐dicarbonyl and [2+2+2] cycloaddition reaction product. Initially, diketone 1a (1.0 mmol) and terminal alkyne 2a (1.2 mmol) were stirred in the presence of 5 mol‐% each of Co III and Cu(OTf) 2 catalyst in dichloroethane (DCE) at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Rawat and co‐workers demonstrated that Cu@Fe 2 O 3 nanoparticles (@ are nanoparticles) prepared by the hydrothermal method can be used as an efficient catalyst for the synthesis of aminoindolizines and pyrrolo[1,2‐ a ]quinolines (Scheme 16). [52] Due to a short reaction time (2 h), good product yields (75–90%) and recycling of the catalyst without significant loss of activity, this method is highly efficient for the synthesis of pyrrolo[1.2‐ a ]quinolines. The authors proposed the reaction mechanism, which involves nanoparticles promoted imine 64 addition to acetylene, propargylamine 65 5‐endo‐dig ring closure and final demetallation of intermediate 66 .…”
Section: Synthesis Of Five‐membered Nos‐heterocyclesmentioning
confidence: 99%